Desdimelita awatschensis a new species of Melitidae Bousfield, 1973 (Crustacea: Amphipoda: Hadziida) from southeastern Kamchatka (Avacha Bay Pacific Ocean) - Labay, Vjacheslav S. (Zootaxa, 2025)
A new amphipod species, Desdimelita awatschensis sp. nov., from the eastern coast of Kamchatka Peninsula (Northwest Pacific, Avacha Bay) is described. The new species is assigned to the genus Desdimelita Jarrett & Bousfield, 1996 in most of the characters: pleon segments smooth above, in the structure of the mouthparts, gnathopod 1 little sexually dimorphic, carpus of gnathopod 1 (male) long, deeper than wide, dactylus of gnathopod 2 (male) without outer marginal setae, bases of pereopods 5–7 large, regular, outer ramus of uropod 3 2-segmented, terminal article small, telson lobes normal, slightly fused basally. The new species have the bifid anterior lobe of the coxa 6 of females as in Desdimelita transmelita Jarrett & Bousfield, 1996, differs from last by the dorsal carination of urosome segment 1 with 3 subequal teeth. It also differs from D. californica (Alderman, 1936) by the structure of gnathopod 1 of male (the shorter, length 1.5 times as width) and by the structure of pereopods 5–7 (carpus short, 2/3 times as long as merus). Keys to the world species of the genus Desdimelita is provided.